1987
DOI: 10.1016/0741-5214(87)90225-4
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of the bilateral amputee

Abstract: One hundred sixteen patients with bilateral amputation as a result of severe ischemia were reviewed to evaluate their rehabilitation potential. Seventy patients were male and 46 were female; ages ranged from 31 to 92 years (mean 68 years). The operative mortality rate after the second amputation was 9.5% (11 of 116 patients). The time from the first to second amputation ranged from zero to 144 months (mean 23 months). Follow-up from 1 to 14 years was available on all patients. Sixty percent of the patients sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…5 Also, previous studies have shown that those who had less time between their amputations had poorer outcomes. 1,5 We found no such correlation at long-term follow-up. Future studies should compare a larger number of patients with BTTA who abandon prosthetic use with those who continue to wear their prostheses, to examine prognostic factors related to long-term prosthetic use.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…5 Also, previous studies have shown that those who had less time between their amputations had poorer outcomes. 1,5 We found no such correlation at long-term follow-up. Future studies should compare a larger number of patients with BTTA who abandon prosthetic use with those who continue to wear their prostheses, to examine prognostic factors related to long-term prosthetic use.…”
Section: Discussionmentioning
confidence: 65%
“…This survival time is similar to previous reports of 2.5-5 yrs after amputation in bilateral lower-extremity amputees. 4,6,7,9,10 Evans et al 1 and Inderbitzi et al 11 also have reported a 2-yr survival rate of 60%-62% and a 5-yr survival rate of 31%-40% 1,11 in patients with bilateral lower-extremity amputation of peripheral vascular causes from acute care. A study by Ebskov 17 examined 10,191 lower-extremity amputations and found that the median survival analysis (by Kaplan-Meier analysis) was 2.6 yrs in those patients with unilateral transtibial amputations from diabetic causes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Rehabilitation of patients with bilateral lower-limb amputation is challenging because of the degree of the structural loss and the need to replace both limbs with prostheses. The success rate of prosthetic rehabilitation in people with bilateral transtibial amputation has been reported to be in the range of 30% 7,8 to 50% 9 and even as high as 60% to 90%, 10 albeit patients tend to use their prostheses less and have lower mobility and lower rates of employment than do persons with unilateral amputations. In addition, the physiological cost of walking with bilateral prostheses is greater than with a unilateral prosthesis.…”
Section: Rehabilitation Of Persons With Bilateral Lower-limb Lossmentioning
confidence: 99%
“…During the earlier years of amputee rehabilitation, when prostheses were not as advanced, prosthetic rehabilitation was suggested only for the population of young patients with bilateral lower extremity (LE) amputations due to level of fitness and motivation [2]. The literature for patients with bilateral amputations has a heavy focus on elderly vascular patients, encompassing several etiologies, who may not desire a high function level postamputation [3]. Many studies used questionnaires as an outcome measure for quality of life, confident prosthetic usage, and successful rehabilitation [4,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%